The Effect of Differentiation and Positioning Strategies on Customer Satisfaction Using Digital Banking Service at PT. Bank Muamalat KC Mamuju - Iwan Adinugroho; Shafwan Nugraha (Universitas Negeri Makassar, 2021)
Competition in the world of Islamic banking today is certainly getting tighter with the emergence of various new Islamic banks. In order to maintain a positive existence, Bank Muamalat as one of the pioneers of Islamic banking in Indonesia certainly requires a strategy to be able to win and retain its customers among the community. The two strategies used are the differentiation strategy and positioning of their digital banking services to be superior to other Islamic banking digital banking products. These two strategies are used to maintain customer satisfaction in the use of digital banking services. This study examines the relationship between differentiation strategy and positioning of digital banking services on customer satisfaction at PT Bank Muamalat Indonesia KC Mamuju. This study uses a quantitative approach. Methods of data collection was carried out using questionnaires, observation, and documentation studies. Research respondents are customers of PT Bank Muamalat Indonesia (BMI) Mamuju Branch Office. The sample used in this study were 97 respondents with accidental sampling technique. The data analysis techniques used in this study were descriptive analysis, validity and reliability tests , classical assumption tests, as well as multiple linear regression analysis and hypothesis testing using the F test (simultaneous) and t test (partial) with the help of SPSS for windows program software. (Statistical Package for Social Science) in processing research data.